Interactions between Vitamin D Status, Calcium Intake and Parathyroid Hormone Concentrations in Healthy White-Skinned Pregnant Women at Northern Latitude - Hemmingway, Andrea (Nutrients, 2018)
Adverse effects of low vitamin D status and calcium intakes in pregnancy may be mediated through functional effects on the calcium metabolic system. Little explored in pregnancy, we aimed to examine the relative importance of serum 25-hydroxyvitamin D (25(OH)D) and calcium intake on parathyroid hormone (PTH) concentrations in healthy white-skinned pregnant women. This cross-sectional analysis included 142 participants (14 ± 2 weeks’ gestation) at baseline of a vitamin D intervention trial at 51.9 °N. Serum 25(OH)D, PTH, and albumin-corrected calcium were quantified biochemically. Total vitamin D and calcium intakes (diet and supplements) were estimated using a validated food frequency questionnaire. The mean ± SD vitamin D intake was 10.7 ± 5.2 μg/day. With a mean ± SD serum 25(OH)D of 54.9 ± 22.6 nmol/L, 44% of women were <50 nmol/L and 13% <30 nmol/L. Calcium intakes (mean ± SD) were 1182 ± 488 mg/day and 23% of participants consumed <800 mg/day. The mean ± SD serum albumin-adjusted calcium was 2.2 ± 0.1 mmol/L and geometric mean (95% CI) PTH was 9.2 (8.4, 10.2) pg/mL. PTH was inversely correlated with serum 25(OH)D (r = −0.311, p < 0.001), but not with calcium intake or serum calcium (r = −0.087 and 0.057, respectively, both p > 0.05). Analysis of variance showed that while serum 25(OH)D (dichotomised at 50 nmol/L) had a significant effect on PTH (p = 0.025), calcium intake (<800, 800–1000, ≥1000 mg/day) had no effect (p = 0.822). There was no 25(OH)D-calcium intake interaction effect on PTH (p = 0.941). In this group of white-skinned women with largely sufficient calcium intakes, serum 25(OH)D was important for maintaining normal PTH concentration.